A framework to apply ISO/IEC29110 on SCRUM - Kittitouch Suteeca (2018)
© 2016 IEEE. During the recent years, small software companies have shown interests to use software development standards to improving their processes and competitiveness. Yet, this can be inconvenient for companies who have no experience in standard or Software Process Improvement (SPI). ISO/IEC29110 is a lightweight software development standard including Project management and Software implementation process. Agile and SCRUM is the most selected software development methodology by small software companies. This work focuses on explaining the relationships between agile practices and a Software Implementation process defined by ISO/IEC29110 version 2011. The main purpose of the study is to exhibit the potential application of this standard to SCRUM software development. The results of this study highlight practical frameworks on each Software Implementation activities as well as indicate the required inputs, outputs, mechanisms, and constraints.